AKTIVITAS ANTIBAKTERI DAN KLT BIOAUTOGRAFI EKSTRAK ETANOL DAUN SISIK NAGA (Drymoglossum piloselloides) TERHADAP Streptococcus mutans - Evi Umayah Ulfa; Desi Sandra Sari; Dhani Wijaya (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Sisik naga (Drymoglossum piloselloides) has been used empirically for dysentry and candidiasis. This diseases were caused by bacteria and fungi. The objective of this research was to evaluate the antibacterial effect and to find out the antimicrobial compound of sisik naga. Leaf of sisik naga was extracted with ethanol 90% by using maseration. This extract were tested for antibacterial activity against Streptococcus mutans using agar difussion. TLC Bioautography methods was used to identify the active compound. Result of antibacterial test showedf ethanolic extract of sisik naga had antibacterial effect against S. mutans. Bioautography showed one spot on Rf =0 give clear zone.